Minimum ID P Wave Velocity Model for the Guanacaste Volcanic Arc, Costa Rica - Araya, María C. (2016)
In this study a minimum 1D model for the Guanacaste Volcanic Arc (CVG) is derived from 475 local earthquakes registered between January 2006 and July 2014 by the Arenal-Miravalles Seismological and Volcanic Observatory (OSIVAM). This velocity model has six layers and covers from the surface to a depth of 80 km. The model has velocities from 3.96 to 7.79 km/s from top to bottom. The station corrections obtained range between -0.28 and 0.45. These corrections show a trend with positive values located over the volcanic arc and negative values located on the forearc, in agreement with the crustal thickness. Three main seismicity clusters were acknowledged from the earthquake relocations, which may be associated with activity on inferred faults. The obtained one dimensional velocity model displays a simplified version for the crustal structure and aim to improve the earthquake location processes performed by the OSIVAM.